Aggregation Behavior of Mixed Micellar System of Dodecyl Sulfate‐Based Surface‐Active Ionic Liquids and Anionic Surfactant in Aqueous Media. Issue 2 (16th December 2020) - Kumar, Harsh; Kaur, Gagandeep
Abstract: Mixed micellization behavior of dodecyl sulfate‐based ionic liquids, i.e., 1‐propyl‐3‐methylimidazolium dodecyl sulfate [C3 mim][DS] and 1‐hexyl‐3‐methylimidazolium dodecyl sulfate [C6 mim][DS] with sodium dodecyl sulfate (SDS), is investigated at (298.15, 308.15, and 318.15) K in aqueous medium. For this, the conductometric measurements are carried out to evaluate the critical micelle concentrations ( cmc ), ideal critical micelle concentration ( cmc *), degree of counterion dissociation ( g ), thermodynamic parameters, micellar mole fraction of ionic liquids, and interaction parameter ( β ) of the mixed system based on the different proposed models given in the literature. Further surface tension measurements have been carried out to confirm the value of cmc obtained via a conductivity study for all the studied systems at 298.15 K. Other surface parameters, such as surface tension at cmc (γ cmc ), surface pressure (ᴨ cmc ), surface excess (Γ max ), and minimum area per molecule (Amin ), have also been evaluated for both the systems. Abstract :